2015
DOI: 10.1007/s12039-015-0868-0
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous acquisition of three NMR spectra in a single experiment for rapid resonance assignments in metabolomics

Abstract: NMR-based approach to metabolomics typically involves the collection of two-dimensional (2D) heteronuclear correlation spectra for identification and assignment of metabolites. In case of spectral overlap, a 3D spectrum becomes necessary, which is hampered by slow data acquisition for achieving sufficient resolution. We describe here a method to simultaneously acquire three spectra (one 3D and two 2D) in a single data set, which is based on a combination of different fast data acquisition techniques such as G-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…These approaches can be classified as experiments that use reduced sampling approaches such as nonuniform sampling (NUS), [31][32][33][34][35][36][37] projection NMR, [29,30] Hadamard NMR, [53][54][55] and phase-modulated (PM) NMR [38] and those based on fast-pulsing techniques [56][57][58][59] such as fast heteronuclear multiple quantum coherence (HMQC). In addition to these two categories, another type of sampling approach involves multiple receivers [29,30] and ultrafast single-scan NMR techniques. [33,[39][40][41][42][43][44][45][46][47][48][49][50][51][52] This is summarized in Table 1.…”
Section: Nmr Data Acquisition With High Sensitivity and Resolutionmentioning
confidence: 99%
See 3 more Smart Citations
“…These approaches can be classified as experiments that use reduced sampling approaches such as nonuniform sampling (NUS), [31][32][33][34][35][36][37] projection NMR, [29,30] Hadamard NMR, [53][54][55] and phase-modulated (PM) NMR [38] and those based on fast-pulsing techniques [56][57][58][59] such as fast heteronuclear multiple quantum coherence (HMQC). In addition to these two categories, another type of sampling approach involves multiple receivers [29,30] and ultrafast single-scan NMR techniques. [33,[39][40][41][42][43][44][45][46][47][48][49][50][51][52] This is summarized in Table 1.…”
Section: Nmr Data Acquisition With High Sensitivity and Resolutionmentioning
confidence: 99%
“…In metabolomics, parallel NMR data acquisition can be used for recording different 2D experiments required for resonance assignments simultaneously. [29,30,74] For instance, the most widely used 2D NMR experiments in metabolomics are as follows: 2D [ 1 H, 1 H] TOCSY, 2D [ 13 C, 1 H] HSQC, and 2D [ 13 C, 1 H] HSQC-TOCSY. These three spectra can be conceptualized as three orthogonal projections (2D planes) of 3D [ 13 C, 1 H] HSQC-TOCSY ( Figure 2).…”
Section: Acquisition With Multiple Receiversmentioning
confidence: 99%
See 2 more Smart Citations
“…13 In such situations, the required multidimensional NMR measurements have to be recorded within the life span of the native state of the protein under study. In this context, several strategies have been proposed: Filter Diagonalisation Method (FDM), 14 Reduced Dimensionality (GFT 15,16 and APSY 17 ), Non-Uniform Sampling (NUS), [18][19][20][21][22] projection reconstruction, 23 Shaped Arrayed data acquisition protocol (SHARC NMR), 24 Hadamard NMR, 25 Ultrafast, 26 Covariance NMR, 27 multiple-receiver techniques, [28][29][30][31][32] longitudinal relaxation optimization, 33,34 cooling overall spin temperature (COST), 35 HSQC-based multi-dimensional out-and-back experiments, 36 Band-Selective Optimized-Flip-Angle-Short-Transient (SOFAST), 37 and Band-selective Excitation Short-Transient (BEST) 38 methods, which help to reduce the nD-NMR experimental times to a signicant extent. Atreya et al 34 have demonstrated the importance of combined implementation of two fast NMR techniques (longitudinal relaxation optimization 33 and GFT 15 ) for obtaining the chemical shi information in short instrumental times.…”
Section: Introductionmentioning
confidence: 99%